2006
DOI: 10.1086/507264
|View full text |Cite
|
Sign up to set email alerts
|

SpitzerIRAC Photometry of M, L, and T Dwarfs

Abstract: We present the results of a program to acquire photometry for 86 late M, L, and T dwarfs using the Infrared Array Camera (IRAC) on the Spitzer Space Telescope. We examine the behavior of these cool dwarfs in various color-color and color-magnitude diagrams composed of near-IR and IRAC data. The T dwarfs exhibit the most distinctive positions in these diagrams. In M 5.8 versus [5.8]À[8.0], the IRAC data for T dwarfs are not monotonic in either magnitude or color, giving the clearest indication yet that the T dw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
315
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(333 citation statements)
references
References 90 publications
(67 reference statements)
16
315
1
Order By: Relevance
“…None of our IRAC detected objects shows a (3.6−4.5) index over ∼0.4, in agreement with the colours expected for high-redshift LBGs. On the other hand, previous studies have found that cool dwarf stars show a broad range in the 4.5 μ luminosity, yielding values in the 3.6−4.5 colour index that can be much larger than those of our objects (up to 2.0 mag, see Patten et al 2006;Helling et al 2008), although lower colour indexes have also been observed for these objects.…”
Section: Detected Z > 65 Galaxiescontrasting
confidence: 85%
“…None of our IRAC detected objects shows a (3.6−4.5) index over ∼0.4, in agreement with the colours expected for high-redshift LBGs. On the other hand, previous studies have found that cool dwarf stars show a broad range in the 4.5 μ luminosity, yielding values in the 3.6−4.5 colour index that can be much larger than those of our objects (up to 2.0 mag, see Patten et al 2006;Helling et al 2008), although lower colour indexes have also been observed for these objects.…”
Section: Detected Z > 65 Galaxiescontrasting
confidence: 85%
“…The solid line represents the spectrophotometric sequence of field mid-M-to late-T-type dwarfs, shifted to match the brightness of the late-M-type cluster members (Zapatero Osorio et al 2008). For the field dwarfs, we use average absolute I-band magnitudes, I − J, and J − K s colours compiled by Caballero et al (2008a) 6 , J − H colours from Vrba et al (2004) 7 , and mid-infrared magnitudes from Patten et al (2006). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5. We compared synthetic spectra to the SED (optical, when available + 2MASS JHK + Spitzer fluxes) of M7-L7 field dwarfs studied in Patten et al (2006). Best fitting solutions were checked visually and were discarded, if needed.…”
Section: Behavior Of Atmospheric Models At the M-l Transitionmentioning
confidence: 99%